2020
DOI: 10.1111/jjns.12376
|View full text |Cite
|
Sign up to set email alerts
|

The role of workplace social capital on the relationship between perceived stress and professional identity among clinical nurses during the COVID‐19 outbreak

Abstract: AimWorkplace social capital refers to relationship networks formed by individuals in an organization through long‐term mutually beneficial interactions and cooperation with members. These relationship networks can create value and resources for organizations and individuals. This current study aimed to explore the potential impact of workplace social capital on the association between perceived stress and professional identity in clinical nurses during the COVID‐19 outbreak.MethodsIn this cross‐sectional study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 68 publications
0
13
0
7
Order By: Relevance
“…A possible reason for such results could be the sudden transition to large-scale WFH practices, which allowed for internal DKS procedures and tools to be available to all employees, regardless of their age, gender, and position, as well as across all organization types (big vs. small, public vs. private), in order to maintain “business as usual” during the pandemic ( Kirchner et al., 2021 ; Waizenegger et al., 2020 ). Following SCT, social relationships between colleagues existed prior to the pandemic ( Zhang et al., 2021 ); hence, the enforced WFH practice did not affect the association between demographics and internal DKS.…”
Section: Discussionmentioning
confidence: 99%
“…A possible reason for such results could be the sudden transition to large-scale WFH practices, which allowed for internal DKS procedures and tools to be available to all employees, regardless of their age, gender, and position, as well as across all organization types (big vs. small, public vs. private), in order to maintain “business as usual” during the pandemic ( Kirchner et al., 2021 ; Waizenegger et al., 2020 ). Following SCT, social relationships between colleagues existed prior to the pandemic ( Zhang et al., 2021 ); hence, the enforced WFH practice did not affect the association between demographics and internal DKS.…”
Section: Discussionmentioning
confidence: 99%
“… Liu et al (2020) shared that Chinese health care providers reported stronger identification to their professional duty since COVID-19. Previous studies have also shown that medical staff with high levels of professional identity might perceive their occupation positively, which may improve their ability to resist stress, thereby reducing their perception of stress ( Zhang et al, 2021b ). When occupational stressors are not perceived as threatening to one sense of self, the stress response may not be activated.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, given the importance of a healthy work environment for patients, nurses, and organizations, researchers and professional organizations have emphasized promoting nurse work environments [ 7 , 9 11 ] . The World Health Organization (2020) called for urgent investment by improving work conditions [ 12 ].…”
Section: Introductionmentioning
confidence: 99%